2021
DOI: 10.1186/s12875-021-01611-9
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists’ experiences of osteoarthritis guidelines in primary health care – an interview study

Abstract: Background Osteoarthritis is a common joint disease, globally. Guidelines recommend information, exercise and, if needed, weight reduction as core treatment. There is a gap between evidence-based recommended care for osteoarthritis and clinical practice. To increase compliance to guidelines, implementation was conducted. The aim of the study was to explore physiotherapists’ experiences of osteoarthritis guidelines and their experiences of implementation of the guidelines in primary health care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…After removing duplicates, 483 studies were screened. Next, 138 studies were evaluated based on their full text, and in the end, 44 qualitative studies [ 7 , 16 , 20 , 23 , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ] were included in the study. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates, 483 studies were screened. Next, 138 studies were evaluated based on their full text, and in the end, 44 qualitative studies [ 7 , 16 , 20 , 23 , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] ] were included in the study. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review included 44 qualitative studies conducted in 14 countries, mostly high-income countries: United Kingdom (27.2 %, n = 12) [ 34 , 36 , 39 , 47 , 49 , 52 , 58 , 62 , [64] , [65] , [66] , [67] ], Sweden (13.6 %, n = 6) [ 38 , 43 , 53 , 54 , 59 , 63 ], Ireland (11.3 %, n = 5) [ 32 , 35 , 40 , 44 , 48 ], Canada (11.3 %, n = 5) [ 7 , 20 , 23 , 37 , 68 ], the Netherlands (9.1 %, n = 4) [ 31 , 42 , 46 , 50 ], Norway (6.8 %, n = 3) [ 33 , 41 , 61 ], South Africa (4.5 %, n = 2) [ 60 , 69 ], Brazil (2.2 %, n = 1) [ 16 ], Chile (2.2 %, n = 1) [ 45 ], Germany (2.2 %, n = 1) [ 56 ], Iran (2.2 %, n = 1) [ 51 ], Spain (2.2 %, n = 1) [ 55 ], Australia (2.2 %, n = 1) [ 70 ], and multiple-countries (2.2 %, n = 1) [ 57 ]. Semi-structured interviews, focus group sessions, or both of them were the common data collection methods, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, some patients might have had their diagnosis for some time, sometimes many years, before participating in SOASP. Reasons for that might vary (patients not wanting to see at PT before, patients not being referred to at PT but to a doctor, all health care professionals not following the guidelines and so on) [42]. This delay in participation in SOASP would affect patients´ adaptation, understanding and coping with their illness and that would impact on their PEI score and their enablement.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise therapy and/or educational intervention is recommended as the first-line treatment for hip or knee OA [ 15 19 ]. However, previous meta-analyses have reported that high-intensity exercise and educational intervention did not improve long-term physical activity in patients with hip or knee OA [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%